Analisis Pengaruh Ekspor, Harga Minyak Dan Kurs Terhadap Inflasi Di Indonesia Tahun 1990-2019 - Huda Einurohmah; Maulidyah Indira Hasmarini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to analyze the influence of exports, oil prices, and exchange rates on inflation in Indonesia. This study employs secondary data obtained from IndexMundi, the World Bank, the Central Bureau of Statistics (BPS), and other supporting institutions during the period 1990-2019. The analysis utilizes regression analysis using the Error Correction Model (ECM) method. Subsequently, tests are conducted within the model using Stationarity Test, R-Square Test, F Test, and T Test. The results of the research indicate that the value of exports has a significant impact on inflation. Oil prices also have a significant influence on inflation. Exchange rates likewise have a significant impact on inflation. The results of the F Test analysis indicate that the independent variables, namely exports, oil prices, and exchange rates, collectively influence inflation in Indonesia.